Connectivity Architecture and Subdivision of the Human Inferior Parietal Cortex Revealed by Diffusion MRI. (18th April 2013) - Ruschel, Michael; Knösche, Thomas R.; Friederici, Angela D.; Turner, Robert; Geyer, Stefan; Anwander, Alfred
Abstract : The human inferior parietal cortex convexity (IPCC) is an important association area, which integrates auditory, visual, and somatosensory information. However, the structural organization of the IPCC is a controversial issue. For example, cytoarchitectonic parcellations reported in the literature range from 2 to 7 areas. Moreover, anatomical descriptions of the human IPCC are often based on experiments in the macaque monkey. In this study, we used diffusion-weighted magnetic resonance imaging combined with probabilistic tractography to quantify the connectivity of the human IPCC, and used this information to parcellate this cortex area. This provides a new structural map of the human IPCC, comprising 3 subareas (inferior parietal cortex anterior, IPC middle, and IPC posterior) of comparable size, in a rostro-caudal arrangement in the left and right hemispheres. Each subarea is characterized by a connectivity fingerprint, and the parcellation is similar to the subdivision reported for the macaque IPCC with 3 areas in a rostro-caudal arrangement (PF, PFG, and PG). However, the present study also reliably demonstrates new structural features in the connectivity pattern of the human IPCC, which are not known to exist in the macaque. This study quantifies intersubject variability by providing a population representation of the subarea arrangement and demonstrates the substantial lateralization of the connectivity patterns of the IPCC.